Genomic Characterization of Carbapenem-Resistant Bacteria from Beef Cattle Feedlots - Sani-; Rahat Zaheer; Krysty Thomas; Sujeema Abeysekara; Travis Haight; Luke Saville; Matthew Stuart-Edwards; Athanasios Zovoilis; Tim A. McAllister (MDPI AG, 2023)
Carbapenems are considered a last resort for the treatment of multi-drug-resistant bacterial infections in humans. In this study, we investigated the occurrence of carbapenem-resistant bacteria in feedlots in Alberta, Canada. The presumptive carbapenem-resistant isolates (n = 116) recovered after ertapenem enrichment were subjected to antimicrobial susceptibility testing against 12 different antibiotics, including four carbapenems. Of these, 72% of the isolates (n = 84) showed resistance to ertapenem, while 27% of the isolates (n = 31) were resistant to at least one other carbapenem, with all except one isolate being resistant to at least two other drug classes. Of these 31 isolates, 90% were carbapenemase positive, while a subset of 36 ertapenem-only resistant isolates were carbapenemase negative. The positive isolates belonged to three genera; Pseudomonas, Acinetobacter, and Stenotrophomonas, with the majority being Pseudomonas aeruginosa (n = 20) as identified by 16S rRNA gene sequencing. Whole genome sequencing identified intrinsic carbapenem resistance genes, including blaOXA-50 and its variants (P. aeruginosa), blaOXA-265 (A. haemolyticus), blaOXA-648 (A. lwoffii), blaOXA-278 (A. junii), and blaL1 and blaL2 (S. maltophilia). The acquired carbapenem resistance gene (blaPST-2) was identified in P. saudiphocaensis and P. stutzeri. In a comparative genomic analysis, clinical P. aeruginosa clustered separately from those recovered from bovine feces. In conclusion, despite the use of selective enrichment methods, finding carbapenem-resistant bacteria within a feedlot environment was a rarity.